2021
DOI: 10.1097/md.0000000000027764
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Qigong Baduanjin exercise in the treatment of depression with insomnia

Abstract: Background: Depression is a common mental illness often associated with insomnia. Baduanjin exercise has been found to improve depressive symptoms and has also been found to have good effects on insomnia. However, there are no rigorous clinical studies to evaluate the effects of Baduanjin exercise on depressed patients with insomnia, so this randomized controlled trial will evaluate the efficacy of Qigong Baduanjin exercise in treating depression with insomnia.Methods: This is a prospective randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…These mental processes may potentially improve cognition, attention, and mood by retaining a pattern of activation of brain regions and connectivity of brain networks ( 26 ). It has been demonstrated that Baduanjin shows effectiveness at both physical and mental levels on mental disorders and some other specific diseases, such as depression, anxiety ( 27 ), insomnia ( 28 ), musculoskeletal pain ( 29 ), chronic obstructive pulmonary disease ( 30 , 31 ), and cancers ( 32 ). However, these studies mainly focused on patients with breast cancer ( 33 , 34 ) rather than those with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These mental processes may potentially improve cognition, attention, and mood by retaining a pattern of activation of brain regions and connectivity of brain networks ( 26 ). It has been demonstrated that Baduanjin shows effectiveness at both physical and mental levels on mental disorders and some other specific diseases, such as depression, anxiety ( 27 ), insomnia ( 28 ), musculoskeletal pain ( 29 ), chronic obstructive pulmonary disease ( 30 , 31 ), and cancers ( 32 ). However, these studies mainly focused on patients with breast cancer ( 33 , 34 ) rather than those with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Fomentando la salud mental, la gestión emocional pre-cama mejorará bajo la mayor presión de sueño, que correlaciona con la menor latencia de inicio (ejercicios mente-cuerpo y aeróbico), permitiendo gozar de una duración del sueño prolongada (Fan et al, 2021;Guan et al, 2021;Xie et al, 2019). Esto se traduce en mayor eficiencia (entrenamiento de fuerza) y en la sensación de haber tenido una buena calidad del sueño subjetiva sin fragmentación (fuerza), promoviendo subsecuentemente la adecuada función diurna (Ramos-Campo et al, 2021;Santiago et al, 2022).…”
Section: Influencia De Los Hábitos Deportivosunclassified
“…Aquellos con niveles más altos de actividad física reportaban aumentos en la fase de ondas lentas (NREM) y en la fase con movimientos oculares rápidos o sueño paradójico (REM) (Kredlow et al, 2015). En concreto, el ejercicio de fuerza se ha vinculado con la estructura (fase NREM) y la duración del sueño (Kovacevic et al, 2018); mientras que el ejercicio aeróbico y los ejercicios mente-cuerpo (estiramientos, yoga, taichí, Qiqong) promueven la disminución del tiempo hasta quedarse dormido (D´Aurea et al, 2018;Fan et al, 2021) y favorecen el sueño REM, además de relacionarse con menores fragmentaciones del sueño y el buen desempeño diurno (Hartescu et al, 2015). Suppiah et al (2015) abogan por la práctica colectiva y la alta intensidad (>80% Frecuencia Cardíaca Máxima), alejadas de horas cercanas al sueño por la sobrexcitación mental que conlleva.…”
Section: Introductionunclassified